Experimental correlations and integration of gas boosters in a hydrogen refueling station. (24th June 2020) - Ligen, Yorick; Vrubel, Heron; Arlettaz, Johnny; Girault, Hubert
Abstract: Air driven gas boosters are often deployed in small scale compression systems. Manufacturers specifications, reporting outlet flow for a fixed inlet pressure, do not reflect the batch operation from a limited source storage. Thus, the dynamic variation of critical process parameters such as efficiency, temperature and flow are not documented. Using a hydrogen refueling station demonstrator, the data from more than 20′000 compression cycles is compiled and analyzed. Experimentally derived correlations are determined for an air driven gas booster feeding a cascade storage. A specific analysis of the clearance volume and the working air pressure is introduced. An engineering tool was developed in MATLAB for performance forecasting. It allows the user to simulate the process trends with an accuracy of ±5%. In the context of a hydrogen refueling station, duration, temperature, compression cycles and air consumption data can be used for process management and maintenance planning. Graphical abstract: Image 1 Highlights: Novel strategy for the characterization of air-driven gas boosters. Performance forecasting for duration, efficiency, and cycles with 5% accuracy. Clearance volume of 5–12%, induces a volumetric efficiency <70% for high ratios. Only half of the air drive pressure is used as working pressure at low ratios.